Analisis Faktor-faktor yang Mempengaruhi Keputusan Pembelian Cabai Rawit Merah (Capsicum chinense jacq) di Pasar Anyar, Kota Tangerang - Yesi Nurvita Sari; Ratna Mega Sari; Ahmad Bukhari (UM Purwokerto Press, 2022)
The purpose of this research is to analyze the effect of price, attitude, income, product quality and sales location on purchasing decisions both partially and simultaneously. This research was conducted in Pasar Anyar, Tangerang City. The study time was conducted in December - Maret 2022. The type of research used is descriptive quantitative research. The sampling technique used in this study was incidental sampling with a total sample of 50 people. The analysis technique used in this study is descriptive statistical analysis, multiple linear regression analysis, classical assumption test and hypothesis test. The results of the t-test (partial) indicate that the product quality variable (X4) have a significance value of < 0,05 and t-test > t-table. It can be concluded that partially the independent variables have a significant effect on purchasing decisions (Y). While the price variable (X1), attitude (X2), income (X3), and sales location (X5) has a significance value of > 0,05 and t-test < t-table. It can be concluded that partially price variable does not affect the purchase decision (Y). The results of the F-test show a significance value of < 0.05 and f-test > f-table. It can be concluded that the variable price, attitude, income, product quality and sales location together have a significant effect on purchasing decisions on Cabai Rawit